Extracellular Monomeric Tau Is Internalized by Astrocytes - Perea, Juan Ramón; López, Esther; Díez-Ballesteros, José Carlos; Ávila, Jesús; Hernández, Félix; Bolós, Marta (Frontiers in Neuroscience, 2019)
Tau is a microtubule-associated protein that is expressed in neurons. However, in a group of neurodegenerative diseases named tauopathies—characterized by an increase in aggregated and/or hyperphosphorylated Tau—the protein accumulates inside other cells, such as astrocytes and microglia. Given that these glial cells do not produce Tau, its presence can be explained by internalization from the extracellular medium and consequent formation of Tau aggregates. Among internalization mechanisms, heparan sulfate proteoglycans (HSPGs) have been proposed to be responsible for fibrillary Tau uptake in various cell types. Here we studied whether monomeric Tau, which has been observed to be internalized by glial cells such as microglia, was also taken up by astrocytes. Although this Tau form was internalized from the extracellular medium by these cells, the mechanism of uptake was found to be independent of HSPGs.